PANDEMIC PIONEERS: HOW JILIN UNIVERSITY STUDENTS' ENTREPRENEURSHIP ADAPTS AND INNOVATES IN RESPONSE TO CRISIS - Ming, Wang Lei; Han, Zhao Yu (International Research Journal of Arts and Communication, 2024)
University students play a pivotal role in a nation's economic progress and future social development. Fostering their innovation and entrepreneurial spirit is a central concern in higher education. This paper reviews research on the determinants of university students' willingness to innovate and embark on entrepreneurial ventures. Scholars have examined factors like entrepreneurial self-efficacy, entrepreneurial education, entrepreneurial attitude, and their interplay. Wang Y S and Ding F (2023) proposed a mechanistic model illustrating how entrepreneurial self-efficacy and entrepreneurial education, with entrepreneurial attitude as a mediating variable, directly influence university students' entrepreneurial willingness. They argue for expanded innovation and entrepreneurial education to bolster this willingness and creating a supportive campus environment to boost entrepreneurial self-efficacy [1]. Wu Z J and Zhou J (2022) have shown that the quality of entrepreneurial platforms not only directly impacts entrepreneurial intentions but also indirectly influences university students' entrepreneurial intentions through the mediating effect of happiness. They highlight the moderating effect of entrepreneurs' personalities in the relationship between entrepreneurial platform quality, happiness, and entrepreneurial intention [2].